Whole-genome bisulfite sequencing reveals the function of DNA methylation in the allotransplantation immunity of pearl oysters - Gu, Zefeng; Yang, Jingmiao; Lu, Jinzhao; Yang, Min; Deng, Yuewen; Jiao, Yu (Frontiers in Immunology, 2023)
Introduction In the pearl culture industry, a major challenge is the overactive immunological response in pearl oysters resulting from allotransplantation, leading to shell-bead rejection and death. To better understand the molecular mechanisms of postoperative recovery and the regulatory role of DNA methylation in gene expression, we analyzed the changes in DNA methylation levels after allotransplantation in pearl oyster Pinctada fucata martensii, and elucidated the regulatory function of DNA methylation in promoter activity of nicotinic acetylcholine receptor (nAChR) gene. Methods We constructed nine DNA methylomes at different time points after allotransplantation and used bisulfite genomic sequencing PCR technology (BSP) to verify the methylation status in the promoter of nAChR. We performed Dual luciferase assays to determine the effect of the dense methylation region in the promoter on transcriptional activity and used DNA pull-down and mass spectrometry analysis to assess the capability of transcription factor binding with the dense methylation region. Result The DNA methylomes reveal that CG-type methylation is predominant, with a trend opposite to non-CG-type methylation. Promoters, particularly CpG island-rich regions, were less frequently methylated than gene function elements. We identified 5,679 to 7,945 differentially methylated genes (DMGs) in the gene body, and 2,146 to 3,385 DMGs in the promoter at each time point compared to the pre-grafting group. Gene ontology and pathway enrichment analyses showed that these DMGs were mainly associated with “cellular process”, “Membrane”, “Epstein-Barr virus infection”, “Notch signaling pathway”, “Fanconi anemia pathway”, and “Nucleotide excision repair”. Our study also found that the DNA methylation patterns of the promoter region of nAChR gene were consistent with the DNA methylomics data. We further demonstrated that the dense methylation region in the promoter of nAChR affects transcriptional activity, and that the methylation status in the promoter modulates the binding of different transcription factors, particularly transcriptional repressors. Conclusion These findings enhance our understanding of the immune response and regulation mechanism induced by DNA methylation in pearl oysters after allotransplantation.